Analyzing the efficacy of conservative versus surgical treatment of chronic mixed blepharitis via laser Doppler flowmetry and interferometry - Tatyana N. Safonova; Natalya P. Kintyukhina (Russian Open Medical Journal)
Objective — To analyze and compare the efficacy of conservative vs. surgical treatment of chronic mixed blepharitis via laser Doppler flowmetry and interferometry. Materials and methods — We enrolled 42 patients (the sample of 84 eyes) with chronic mixed blepharitis in the study. Laser Doppler flowmetry (LDF) was used to assess the microcirculation in the eyelid skin; interferometry was employed to evaluate the lipid layer of the tear film. Patients in the treatment group were treated by meibomian gland probing (MGP) and by artificial tears with a lipid component, introduced 4 times a day for 30 days. Subjects in the control group had their eyelid massaged in addition to administration of artificial tears. Treatment efficacy was monitored at 1 week, 1.5 months and 3 months. Results — MGP demonstrated a statistically significant positive effect, which persisted for 3 months after the procedure: specifically, the restoration of the tear film stability by increasing the thickness of its lipid layer by 0.27-0.5 μm. When comparing the interferoscopy results, an increase in the area of the lipid layer absence was detected in the control group. Analysis of LDF results showed a decrease in neurogenic and myogenic rhythms, as well as in the blood flow coefficient of variation in both groups. The lymph flow coefficient of variation remained stable in the treatment group, while it tended to decrease in the control group. Conclusion — The obtained data analysis on the basis of objective instrumental assessment of the eyelid morphofunctional state by the methods of interferoscopy and LDF suggested that conducting MGP was more effective in chronic mixed blepharitis treatment, compared with performing an eyelid massage.